A History of International Political Theory - Behr, Hartmut. author. aut Link
XII, 302 p.
Keywords: Contemporary theory of international politics faces a twofold problem: the critical engagement with legacies of national power politics in connection to 20th Century International Relations and the regeneration of notions of humanity. This book contributes to this engagement by a genealogy of thoughts on war, peace, and ethics.